National Policy on Permanent Education in Health: aspects that make up the profile of professionals who work in the Regional Teaching-Service Integration Commissions (CIES) in Pará (Research, Society and Development, 2022)
This article proposes to analyze aspects that make up the profile of professionals who work in the Education Service Integration Commissions (CIES) in the Health Regions in Pará, considering the importance of the functioning of these commissions for the advancement of PNEPS in the state. It was a case study research, with qualitative analysis of an exploratory nature. The research subjects were the 25 professionals who worked in Permanent Education in Health at SESPA with activities directed to the Regional CIES, in the 13 Regional Health Centers. Self-administered online questionnaires were used. The findings showed high adherence of participants to the research; the average time working at CIES Regional is 2 years; a high level of schooling was identified; the majority are part of the category of health professionals; all participants reported having a stable relationship and attributed a high degree of importance to the functioning of the CIES. The need for further research in this area was concluded, however, the present study proposed to analyze the aspects of the profile of these professionals to add efforts with information that can contribute to the spheres of state management for the development of measures that are aligned the consolidation of PNEPS as a public policy.